Competition diet strategies of Olympic athletes - Pelly, F.; O'Connor, H.; Denyer, G.; Caterson, F. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
This study investigated the competition diet strategies of Olympic athletes via a questionnaire distributed within the dining hall at the Sydney 2000 Olympic games. Of the 571 distributed questionnaires, 172 were eliminated due to poor completion rates (<50%) and/or obviously inconsistent responses, leaving a total of 399 (4% of total athlete population). Responses were received from 78 countries (39.0%) with 31 of the 36 Olympic sports (86.1%) represented. The mean age of respondents was 26.2 yrs (range 12-50 yrs), with 44.1% male and 55.9% female. The majority of respondents (81.6%) reported eating the same or more carbohydrate prior to competition. A significantly higher proportion of participants in aesthetic/weight category sports reported eating less food (54.1%), less carbohydrate (29.7%) and less protein (43.2%) prior to competition compared to those participating in endurance/team sports (p<0.001). More than one third of athletes reported always (36.8%) or sometimes (35.2%) taking supplements. Significantly more Australian athletes (41.9%) reported never or rarely using supplements compared to athletes from other countries (25.3%) (p=0.028). Reported fluid intake prior to competition was significantly associated with the type of sport (p<0.001). Over 50% of endurance/team sport athletes reported increasing fluid intake compared to 20% from aesthetic/weight categories, 30.1% of whom reported decreasing fluid consumption. A significantly higher (p=0.014) proportion of Australian athletes (56.5%) reported increasing their fluid intake prior to competition compared to athletes from other countries (38.5%). Athletes obtained their nutrition information from a variety of sources, predominantly books (43.3%), sports dietitians (30.3%), magazines/ fliers (28.0%) and other athletes (25.3%).